Green human resource management implication on increasing productivity of small and medium enterprises - M Astuti; H C Wahyuni (Institut Teknologi Sepuluh Nopember, 2018)
Small And Medium Enterprises (SMEs) is an economic sector that has an important role for economic growth in Indonesia. The level of employment in SMEs, resulting in the role of labor is very influential for SMEs. On the other hand, environmental issues have become an significant factor for the development of SMEs. Therefore, to ensure the sustainability of the business, it is necessary to introduce environmental and social aspects within the framework of the business. Environmental management at the operational processes of business (SMEs), has a positive influence on the sustainability of SMEs in the short term and long term. Green human resource management (Green HRM) is one tool that can be used to manage labor SMEs involving environmental aspects. This study aims to determine the implementation of green HRM in SMEs. The method used is observation and interviews conducted in three SMEs in Sidoarjo. Results showed that SMEs owners do not understand the implementation of green HRM indicated that the working patterns of employees who do not pay attention to the environment.